Design and implementation of civil aircraft test database for multi-discipline integration - LI Xinyang; FENG Yunwen; LI Jian; LU Cheng; XIE Yajun; YANG Li (Hangkong gongcheng jinzhan)
Civil aircraft full-life cycle test data，as a crucial component reflecting test information，establishes a solid foundation for supporting the quality and efficiency of model development. However，due to its substantial data volume and its coverage of multiple professional domains，the lack of comprehensive management leads to a waste of data resources. To address this issue，a set of test data management business processes based on airworthiness regulations is proposed to effectively manage multi-disciplinary civil aircraft test data. And the study proceeds with the design and implementation of a database. Firstly，a survey of the research needs of the technical center personnel is conducted，followed by a comprehensive analysis of the database's functionality based on the survey results. Subsequently，architecture design is carried out，considering specific business requirements for storing multi-disciplinary test data，as well as market-relevant database development technologies. The logical relationships between the storage content of various test modules are clarified，then the flight module serving as an example is taken for detailed database module design. Finally，a database operating interface is constructed to validate the feasibility of the design，offering valuable insights for the design of a multi-disciplinary test database.